2022
DOI: 10.1016/j.psj.2021.101626
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin exerts its antiviral activity against infectious bronchitis virus by inhibiting the deubiquitinating activity of papain-like protease

Abstract: Infectious bronchitis virus ( IBV ) is a causative agent that causes severe economic losses in the poultry industry worldwide. Papain-like protease ( PLpro ) is a nonstructural protein encoded by IBV. It has deubiquitinating enzyme activity, which can remove the ubiqutin modification from the protein in nuclear factor kappa-B ( NF-κB ) and interferon regulatory factor 7 ( IRF7 ) signaling pathway, so as to negatively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Compound 20 showed higher inhibitory effect than compound 18 [ 41 ] . Myricetin 21 depicted an apparent restrained effect on infectious bronchitis virus (IBV)at 100 μmol/mL, attenuating the IBV activity closely 50% at 10 μmol/mL by regulating nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and interferon regulatory factor 7 (IRF7) pathways [ 44 ]. Different influenza virus evaluations were performed using Quercetin-7-O-glucoside 25 , and the result showed there was a strong inhibitory effect on virus strains with IC 50 of 3.1 to 8.19 µg/mL, accompanied with the decrease of influenza-induced reactive oxygen species and autophagy [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 20 showed higher inhibitory effect than compound 18 [ 41 ] . Myricetin 21 depicted an apparent restrained effect on infectious bronchitis virus (IBV)at 100 μmol/mL, attenuating the IBV activity closely 50% at 10 μmol/mL by regulating nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and interferon regulatory factor 7 (IRF7) pathways [ 44 ]. Different influenza virus evaluations were performed using Quercetin-7-O-glucoside 25 , and the result showed there was a strong inhibitory effect on virus strains with IC 50 of 3.1 to 8.19 µg/mL, accompanied with the decrease of influenza-induced reactive oxygen species and autophagy [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…MYR shows abundant resource advantages and huge potential utilization value. Multiple effects of MYR have been reported to depend on the therapeutic dose [ 22 ]. Cell viability assay indicated that the higher dose of MYR (40 and 80 μM) significantly inhibited cell growth, while the lower dose groups (10 and 20 μM) showed no cytotoxicity on NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid affects IBV replication by upregulating MDA5, MAVS, TLR7, MyD88, IRF7, IFN-α, and IFN-β in the trachea and lung ( Abaidullah et al., 2021 ). Myricetin exerts antiviral effects on IBV by enhancing ubiquitin modifications of TRAF3 and TRAF6, which PLpro inhibits, and upregulating the activation of the IRF7 signaling pathway ( Peng et al., 2022 ). The present study shows that RIP increased the downstream expression of IFN-β via increasing the MDA5, TLR3, STING, MyD88, and IRF7 signaling pathways in the kidney and CEK cells to resist viral infection, similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%